Acoustical Characteristics in Restaurants and Food Courts / Large Dining Areas with Varying Levels of Occupancy - Lorimer, Alex; Tinianov, Jessica (Canadian Acoustics, 2015)
Dining areas vary in type from quiet and intimate to very lively, and the acoustical character varies as well. Large spaces tend to be more lively and see more transient occupancy, but the designs often try to balance a more intimate setting for conversations, while retaining a dynamic and exciting atmosphere. The atmosphere will also vary depending on the type of space: the acoustical character will differ in food courts, smaller, more intimate restaurants, and urban restaurants with lively bar areas. In spaces without significant amplified background music, the sound level is dominated by speech, and communication quality is therefore of importance. The acoustic properties of such spaces are strongly affected by the occupancy level, due to the changes in reverberation and ‘self-noise’ or ‘din’ of the occupants themselves. Recent field measurements and experience with several dining spaces at varying levels of occupancy are reviewed herein.